2001
DOI: 10.1111/j.1741-3737.2001.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Family Time: From Ideology to Lived Experience

Abstract: “Family time” is often uncritically accepted as a uniform, coherent concept and a universally desirable goal. In order to fully understand the meaning of family time in experience, interviews were conducted with parents in 17 dual‐earner and 11 single‐parent families, and 8 observation episodes were done with 4‐ and 5‐year‐old children in childcare. What emerged was a dramatic discordance between the expectations and experiences of family time. Although families have held on to an expectation of a positive exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
221
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(245 citation statements)
references
References 19 publications
(17 reference statements)
15
221
1
8
Order By: Relevance
“…One of the strongest forces in contemporary family life is the increased striving by both genders towards the ideal of a family life characterized by parents and children who enjoy high quality relationships marked by closeness, responsiveness, and shared activity (Coontz, 2005;Daly, 2001;Mintz, 2004;Tubbs, Roy, & Burton, 2005). To balance their concerns that work interferes with participation in family life, many parents specifically set aside "family time" to promote positive and memorable family experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strongest forces in contemporary family life is the increased striving by both genders towards the ideal of a family life characterized by parents and children who enjoy high quality relationships marked by closeness, responsiveness, and shared activity (Coontz, 2005;Daly, 2001;Mintz, 2004;Tubbs, Roy, & Burton, 2005). To balance their concerns that work interferes with participation in family life, many parents specifically set aside "family time" to promote positive and memorable family experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-earner parents with children worry about the effect of work hours on children and family relationships and strive to cope by focusing on ritual family interactions like dinners or organized leisure (Daly, 2001;Ochs et al, in press;Kremer-Sadlik & Paugh, 2007). Many report that they would choose to work fewer hours if given the opportunity (Jacobs & Gerson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…General late-modern tendencies of reflexive individualization, transformation of intimacy and a general time-pressure in families (Bonke, 2002;Dencik and Schultz Jørgensen, 1999;Giddens, 1991Giddens, /1992Daly, 2001;Hochschild, 1997;Jensen, 2001;Kristjánsson, 1999) may encourage this tendency for parents to ferry their children. The reflexive individual planning is also current among children, who plan their every day mobility with parental ferrying in mind.…”
Section: His Childhood Has Definitely Been Different From Mine I Havmentioning
confidence: 99%
“…The authors acknowledge the contributions of Daly (2001) in regards to the conceptualization of family time, but they suggest that further research should focus on parental feelings regarding the time that is actually spent with their children.…”
mentioning
confidence: 99%
“…In the preface to his book, Families & Time, Daly (2001) reflected on his work with young fathers and their children. From his research, he observed that these fathers often lamented about the scarcity of time with their children, wondering how they could spend more time with their children, and how they could manage to make more time for their children.…”
mentioning
confidence: 99%